2016
DOI: 10.1186/s40152-016-0046-0
|View full text |Cite
|
Sign up to set email alerts
|

Fish as a ‘bridge’ connecting migrant fishers with the local community: findings from Okinawa, Japan

Abstract: Migration is part of fishers' livelihood strategies, and the topic of 'migration and fisheries' has gained considerable attention from researchers. Previous works identified negative and positive impacts of migrant fishers on local communities. However, little attention has been given to how social relationships are actually built between migrant fishers and local residents. This paper is based on observations of daily life and social connections in a coastal village in Okinawa, Japan and aims to fill this gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The other half takes place in small-scale fisheries, which employ over 90% of the world's fishers and fish workers, and provide livelihoods for some 120 million people, primarily in low-income countries (Kelleher et al, 2012;Teh and Sumaila, 2013;FAO, 2015;Teh et al, 2020). Small-scale fisheries are also characterized by diversity, with many shaped by locally developed management practices such as community fisheries co-management (Sen and Raakjaer Nielsen, 1996), locally managed marine areas in the Pacific (Metai, 2018), caletas in Chile (Castilla et al, 1998), and utaki in Okinawa (Sugimoto, 2016). While the study of how stewardship manifests in these settings provides insights into the role of knowledge, customs and management structures, the link between stewardship and environmental sustainability in small-scale fisheries remains ambiguous (McConney et al, 2019;Björkvik, 2020).…”
Section: From Sustainable Seafood To Stewardshipmentioning
confidence: 99%
“…The other half takes place in small-scale fisheries, which employ over 90% of the world's fishers and fish workers, and provide livelihoods for some 120 million people, primarily in low-income countries (Kelleher et al, 2012;Teh and Sumaila, 2013;FAO, 2015;Teh et al, 2020). Small-scale fisheries are also characterized by diversity, with many shaped by locally developed management practices such as community fisheries co-management (Sen and Raakjaer Nielsen, 1996), locally managed marine areas in the Pacific (Metai, 2018), caletas in Chile (Castilla et al, 1998), and utaki in Okinawa (Sugimoto, 2016). While the study of how stewardship manifests in these settings provides insights into the role of knowledge, customs and management structures, the link between stewardship and environmental sustainability in small-scale fisheries remains ambiguous (McConney et al, 2019;Björkvik, 2020).…”
Section: From Sustainable Seafood To Stewardshipmentioning
confidence: 99%
“…On the Okinawan Islands, there is a belief in the existence of a "paradise" over the ocean called "Niraikanai," where one should never reach for anything thanks to the bountiful gifts available to the community, such as schools of fish, agricultural products, precious driftage, visitors who bring new techniques and cultures, and various other blessings (Nakamatsu 1990). Thus, as can be seen from the region's history and customs, the coastal communities on Okinawa consider the common village seas having economic, social, and cultural values (Sugimoto 2016) (also see Photo 1). More recently, particularly since 1980, marine tourism has become an important industry on Ishigaki and the other Okinawan Islands, as mentioned above.…”
Section: Human-ocean Relations On the Islandmentioning
confidence: 99%
“…Compared with the source (mother) population (Ministry of Internal Affairs and Communication 2015), the average age of the survey participants was slightly higher than that in the mother population, and the proportion of female residents among the participants was apparently less than that in the mother population. Even though official statistics were not available for the proportion of local and immigrant residents, one community official reported that the local population was around 60% of the total population (Sugimoto 2016). Additionally, although there were no official statistics or published/gray literature on the average length of residence, 19.2(years) or more should be considered as the appropriate time frame that sufficiently represents the perspective of the locals.…”
Section: Demographic Structure Of Survey Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many types of uses in the Sekisei Lagoon. Traditionally, the fisheries resources at the very nearshore coastal area have been utilized by the local people at the daily basis and it constitutes an important part of local culture (Sugimoto 2016). The main commercial uses are the fishery and tourism.…”
Section: Ocean Policy In Japanmentioning
confidence: 99%